Emulsion freezing/freeze-drying technique to fabricate scaffold for bone tissue engineering using biodegradable polymer - Masturah Mohamed Mokhtar, 1989-, author; Naznin Sultana, supervisor; Fakulti Kejuruteraan Bioperubatan dan Sains Kesihatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Kejuruteraan (Bio - Perubatan)) - Universiti Teknologi Malaysia, 2012